PELATIHAN PEMBUATAN HANDY CRAFT UNTUK GURU-GURU SLTP DI DAERAH ISTIMEWA YOGYAKARTA - Zuni K, Enny; Yuh Suprihatin, Emy; Bariqina, Endang (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
This  Community    Service   Program   is  intended   to  (1)  provide   knowledge    and skills  on  local  content   subject-matter    PKK  for  Junior  High  School  teachers,   such  as handycraft   which   is made  from  natural  materials,   textile,   and  recycled   materials,   (2) develop   the  PKK  teachers'    creativity   in handycraft    making   for  Junior   High  School students.This   training    uses   classical    approach    for  teoritical    material   and   individualapproach   for practical   material.   In oeder  to get optimal  results,  an intimate   individual guidance   is provided   during  the  practical   process.   Evaluation   is performed   during  the practical   process,   practical   outcomes,   and post-training   periods.Outcomes    of  this  training   are  handicraft    products   such  as:  (l)  picture   framefrom  cardboard   covered  with  dried  leaves,  (2) mascot   from  batik's  scraps,   (3)  buffetdecoration   from  bathing  soap  and water  lace,  (4) pencil  cap from  flannel,  and  (5) free style  works,  such  as accessories   from  banana  stem  and tissue  box from  used  ice cream spoon.   Results   of  the  evaluation    on  the  participants'     works   show  that  42  %  of  the participants'    reach  the  excelent   category.  The  observation   performed   after  the  training show   that   90%   of  the   participans     have   implemented     the   training    outcomes.the material    most   frequently    implemented     for  the  junior   high   school   sudents    in  the making  of picture   frame  from  cardboard   and  dried  leaves,  where  as the  least  frequent materials   implemented    is book  self  decoration   form  bathing  soap  and  water  lace.  This is  due  to  the  relatively   high  price  of  the  material   and  need  more   difficult   material preparation   than  the  others.   The  participants'     responses   during  the  training   are  very good,  these   are  proved   by  their  enthusiasm    and  determination     in  performing    tasks given  by their  respective   instructor   as well  as the  participants'    comments   about  their impression   and  messages   indicating   that  this  training   can  open  the  insight  and  blow fresh  wind  for the  local   content  subject-matter    PKK. Key words: handicraft.